The performance of externally managed REITs in Asia: further evidence from free cash flow and agency costs - Wei, Lan Chong; Kien, Hwa Ting; Fan, Fah Cheng (Emerald Publishing Limited, 2017)
Purpose: The purpose of this paper is to examine the impact of free cash flow (FCF) on the agency costs and how these FCF and agency costs affect the performance of REITs in Asia. Unlike previous studies that focus on conventional public listed companies and non-regulated industry, the Asian REIT industry being a highly regulated industry provides a new context for further research. Design/methodology/approach: The samples for this study comprise REIT data from four major Asian REIT countries, namely, Japan, Singapore, Hong Kong and Malaysia. These countries are the leaders in Asian REITs which account for 94 percent of the total market capitalization of REITs in Asia. The study period is from 2002 to 2012 using panel data. This study employs GMM method which is more robust compared to previous studies that used pooled ordinary least squares (OLS) and other panel data methods. Findings: The results indicate that FCF and agency costs persist over time in Asian REITs even though REITs are in a highly regulated industry. The findings also imply that REIT managers face substantial costs when they wish to adjust to the equilibrium level of agency costs, whereby the optimum level is always dynamic and not constant over time and moves with the changes in the determinants of agency costs. These agency costs persist over time and have significant impacts on the performance of REITs in Asia. Research limitations/implications: There are limited data in selling, general and administrative expenses in Asian REITs which render only limited use of selling, general and administrative expenses ratio in this empirical study on Asian REITs. For future research, researchers can embark on research studies on issues that might determine the speed of adjustment toward the equilibrium level of agency costs in Asian REITs. Practical implications: For REIT regulators in Asia, this empirical study helps to provide useful information for policy planning and formulation in REIT corporate governance; and to transform the inherent satellite structure of the externally managed REIT structure into internally managed REIT structure. For REIT managers and practitioners, this empirical study serves as a reflection for them which helps them to be more aware of the dynamism of FCF and agency costs in REITs; and alert them that these FCF and agency costs persist over time which can have significant impacts on the REIT performance, return on assets and return on equity, REIT value and REIT return, respectively in Asia. Thus, they could consider internalizing their REIT management structure for better and more efficient management in REITs in order to mitigate the agency costs that are persistent over time. As a whole, this empirical study contributes significant benefits to all level of the REIT industry in Asia. Social implications: This implies that the REITs in Asia should consider internally managed REIT structure since the agency costs persist over time and there are always dynamic and not constant over time and moves with the changes in the determinants of agency costs. The findings also imply that the regulators in Asian REITs should enforce absolute stringent corporate governance rules and regulations in order to govern the existing inherent satellite structure of the externally managed REITs in Asia. Originality/value: This empirical study contributes significant benefits to all levels of the REIT industry in Asia and the current limited literature on Asian REITs by examining the impact of FCF and agency costs on the performance of REITs in Asia. This is the first research to embark on FCF and agency costs on REITs in Asia. Furthermore, this study employs GMM method which is more robust compared to previous studies that used pooled OLS and other panel data methods.